Chaos in Ideas, Hastiness in Action: A Critical Review of Politics and Government in the Middle East - Seyed Abdolamir Nabavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Increasing the enthusiastic attempts to trace the Middle East events and evolutions, on the one hand, and establishing the Middle East Studies courses (both in research and teaching) on the other hand, caused the need for research and teaching sources in this field. The printing of Politics and Government in THE Middle East by a reputable university press is very important; a book which is going to have educational methods and offer the data and analyses on political issues to the students of political sciences, especially the bachelors. However, reviewing the form and the content of this book shows that despite the publishers’ finesse to offer a scientific and comprehensive work, it has some weaknesses and inaccuracies, so that introducing it as an academic source may be hesitated. Accordingly, this paper offers some positive and negative aspects of the book, and at the end, it proposes a recommendation to the authors and publishers to issue a new edition of the book. The major drawback of the book seems to be its lack of the proficiency guidelines and ideas of the scholars of the Middle East Studies as well as and guidelines and ideas of education.